Association of tumour necrosis factor-alpha, lymphotoxin-alpha and HLA-DRB1 gene polymorphisms with Löfgren's syndrome in Czech patients with sarcoidosis - Mrazek, F; Holla, L I; Hutyrova, B; Znojil, V; Vasku, A; Kolek, V; Welsh, K I; Vacha, J; du Bois, R M; Petrek, M (Tissue antigens, 2005)
Sarcoidosis is a granulomatous disorder showing a clear association with MHC (HLA) class I and class II genes. In order to investigate whether polymorphisms of nearby pro-inflammatory genes located within the MHC class III region may also contribute to susceptibility to sarcoidosis or to its clinical manifestation, tumour necrosis factor-alpha (TNF-alpha) and lymphotoxin-alpha (LT-alpha) genes were chosen for analysis in a case-control association study. In order to evaluate the findings on the TNF-alpha and LT-alpha genes in connection with the closely linked MHC class II region, 'classical' HLA-DRB1 locus was also investigated. Polymerase chain reaction-based methodologies were used in order to characterize two single-nucleotide polymorphisms (TNF-308*G/A and LTAlpha+252*A/G) and HLA-DRB1 allele groups in 114 Czech patients with pulmonary sarcoidosis and 425 healthy controls. LTA+252*G and HLA-DRB1*13 allele carriers were more frequent in patients, compared to those in controls. By contrast, HLA-DRB1*07 carriers were less frequent among sarcoidosis patients. The overrepresentation of TNF-308*A, LTAlpha+252*G and HLA-DRB1*03 allele carriers was found in a subgroup of sarcoidosis patients presenting with Lofgren's syndrome (LS) by comparison with the subgroup of patients without LS (NLS; phenotype frequency LS vs NLS: 68.8 vs 37.1% for TNF-308*A, 93.8 vs 66.3% for LTA+252*G and 68.8 vs 21.3% for DRB1*03). The data suggest that the LTAlpha and HLA-DRB1 genes themselves or a gene located nearby contributes to the susceptibility to sarcoidosis and that TNF-308*A, LTA+252*G and HLA-DRB1*03 alleles are associated (directly or via linkage with unknown causative locus) with LS as a specific manifestation of the disease.
Keywords: Polymorphism, Single Nucleotide; Humans; Case-Control Studies; lidé středního věku; lymfotoxin-alfa; Sarcoidosis, Pulmonary; HLA-DRB1 řetězec; studie případů a kontrol; jednonukleotidový polymorfismus; Female; Aged; dospělí; Syndrome; senioři; lidé; HLA-DRB1 Chains; HLA-DR antigeny; TNF-alfa; Adult; HLA-DR Antigens; ženské pohlaví; Male; syndrom; Middle Aged; Adolescent; genetická predispozice k nemoci; Genetic Predisposition to Disease; Czech Republic; plicní sarkoidóza; Aged, 80 and over; Tumor Necrosis Factor-alpha; senioři nad 80 let; Česká republika; mužské pohlaví; Lymphotoxin-alpha; mladiství